2015
DOI: 10.5664/jcsm.5014
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Therapy for Obstructive Sleep Apnea in Children

Abstract: Introduction: Over the last decade, high-fl ow nasal cannula (HFNC) therapy has become an increasingly important and popular mode of noninvasive respiratory support. HFNC facilitates delivery of humidifi ed and heated oxygen at a high fl ow rate and generates positive airway pressure. Methods: We present fi ve cases of children with OSA without adenotonsillar hypertrophy who were treated with HFNC. Results: We demonstrated a statistically signifi cant improvement in apnea-hypopnea index and nadir oxygen satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 22 publications
3
36
0
4
Order By: Relevance
“…Our protocol included sleep staging, sleep architecture, heart rate, and transcutaneous CO 2 monitoring, which has not been previously reported. Compared to a recent similar study 28 our population is larger in size and more homogeneous in age.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our protocol included sleep staging, sleep architecture, heart rate, and transcutaneous CO 2 monitoring, which has not been previously reported. Compared to a recent similar study 28 our population is larger in size and more homogeneous in age.…”
Section: Discussionmentioning
confidence: 66%
“…Though the long-term safety has not yet been studied, data thus far 19,22,23,28 suggest that treating OSA with HFNC has minimal risk and is likely preferable to non-adherence to CPAP. Whereas CPAP has been associated with impaired midface development due to pressure on the maxilla, 12 this nasal cannula is unlikely to cause similar adverse changes due to the open nasal prong design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturnal NPPV normalises the AHI and desaturation index, and improves inspiratory muscle synchrony [135,136]. Limited data support the use of high-flow nasal cannula therapy in children with nCPAP intolerance [137]. b) During periods of upper respiratory infection, nCPAP may be interrupted for a few days due to nasal obstruction and mouth leak [134].…”
Section: 5mentioning
confidence: 99%
“…Joseph et al reported their experience with the use of domiciliary high‐flow nasal cannula in a case series of five pediatric patients aged 2 months to 15 years with severe OSAS. They observed a dramatic improvement in clinical signs and PSG respiratory indices of OSAS in all patients.…”
Section: Introductionmentioning
confidence: 99%